Klasterisasi Produktivitas Tangkapan Rajungan Berdasarkan Usia Nelayan Menggunakan Algoritma K-Means di Kecamatan Pantai Lunci - Adha Susanto; Muhamad Syukron (Jurnal Ilmiah Samudra Akuatika, 2026)
The ability to achieve optimal blue swimming crab catches is influenced by the age of the fishermen. Fishermen of productive age generally exhibit better working capabilities, supported by more optimal physical conditions and greater experience in conducting crab-catching activities. Therefore, this study aims to cluster blue swimming crab catch volumes based on the fishermen's age. This research utilizes the K-Means Algorithm method. The data used as samples for crab catch production were obtained through interviews and questionnaires with 64 fishermen in the Pantai Lunci District. The results revealed three distinct clusters of monthly crab catch volumes. Cluster one consists of catch volumes ranging from 75–150 kg/month by fishermen aged 26–65 years. Cluster two includes catch volumes ranging from 168–300 kg/month by fishermen within the age range of 28–53 years. Cluster three represents a catch volume of 500 kg/month by fishermen within the age range of 33–42 years. This 3-group clustering model provides an optimal value with a silhouette score of 0.846.